Comparison of bleeding following gastrointestinal endoscopic biopsy in patients treated with and without direct oral anticoagulants - Konishi, Takaaki; Ono, Sachiko; Okada, Akira; Matsui, Hiroki; Tanabe, Masahiko; Seto, Yasuyuki; Yasunaga, Hideo (Endoscopy International Open, 2023)
Background and study aims Despite the widespread use of direct oral anticoagulants (DOACs), the association between DOAC use and complications (e. g., bleeding) following gastrointestinal endoscopic biopsy remains unclear. This study aimed to evaluate complications after biopsy in patients treated with DOACs in Japan, where biopsies would be generally performed without DOAC withdrawal based on guideline recommendations.Patients and methods Using a Japanese nationwide database, we identified patients taking DOACs who underwent gastrointestinal endoscopic biopsy (n  = 2,769, DOAC group) and those not taking DOACs (n = 129,357, control group) from April 2015 to November 2020. We conducted 1:4 propensity score (PS) matching and overlap PS-weighting analyses with adjustment for background characteristics to compare occurrence of post-procedure hemorrhage and stroke within 1 week after biopsy, and thrombin use on the day of biopsy without a diagnosis of hemorrhage.Results In total, 578 patients (0.44 %) developed post-procedure hemorrhage, and 13 patients (0.01 %) developed stroke. The DOAC group had more comorbidities than the control group. The PS matching analysis revealed no significant differences in post-procedure hemorrhage (odds ratio, 1.52 [95 % confidential interval, 0.96–2.41]) or stroke (1.00 [0.21–4.71]), whereas the DOAC group received thrombin more often than the control group (1.60 [1.30–1.95]). The results were equivalent in the overlap PS-weighting analysis.Conclusions The PS analyses showed no significant differences in complications following gastrointestinal endoscopic biopsy between DOAC users and non-users. These results suggest the safety of endoscopic biopsy without DOAC withdrawal although the need for careful hemostasis remains.